Disfunção temporomandibular e a terapia miofuncional: uma revisão de literatura - Souza, Laura Vieira (2023)
Introduction: Temporomandibular dysfunction is a change resulting from disorders in the temporomandibular joint, in addition to this structure, the skull and masticatory muscles are affected by the dysfunction. Objective: To investigate in the literature the effectiveness of speech therapy intervention through orofacial myofunctional therapy in patients with this dysfunction. Method: A narrative review of the literature, developed through the Pubmed, Google Academico and Lilacs databases, using the descriptors “temporomandibular joint”, “temporomandibular dysfunction” and “orofacial myofunctional therapy in temporomandibular dysfunction”. Articles were included that related speech therapy approaches in isolation or in association with other approaches. Results: A total of 373 articles were identified, of which 23 articles were selected from reading the full text, 18 were excluded according to the exclusion criteria and 5 articles were included. Conclusion: The studies analyzed in this review described advantageous results on orofacial myofunctional therapy alone or in combination in patients with temporomandibular disorders.